Effect Different Extracts of Tribulus Terrestris on Ammonia Volatilization in Loamy Soil - Sfook, Asaad Abdullah; Neghamish, Razzaq Ghazi (International Journal of Psychosocial Rehabilitation, 2020)
-The study was tested by studying effect of three different plants extracts on ammonia volatilization and number of bacteria after addition extracts to soil with urea in lraqi loamy soil. Three plants extracts of (Olea europaea, lepidium aucheri, Tribulus terrestris) were tested on many isolated bacteria from soils (Bacillus cereus, Bacillus spp, Proteus mirabilis, Proteus vulgaris, Klebsiella pneumoniae, pseudomonas aeruginosa, E.coli Staphylococcus aureus). All bacteria were classificated on (Schwartz et al, 1965) and biochemistry test to different this bacterium. The results explained that all parts of Tribulus terrestris extracts caused decreasing number of isolated bacteria from soil after addition urea and extracts to loamy soil and were reduction ammonia volatilization from soil but other plants extracts Olea europaea and lepidium aucheri didn’t cause any reduction with number of isolated bacteria and ammonia volatile after addition to soil. So this reason was excluding this extracts from using to test against ammonia volatilization but all parts of Tribulus terrestris gave a significantly difference activity of reduction ammonia volatile (p α 0.05) from soil compared with control. Seeds with alcoholic extract was the best treatments at reduction number of bacteria and volatile ammonia. Increasing concentration of extracts caused a significantly reduction (p α 0.05) with ammonia volatilization and number of bacteria